Antioxidant Content and Partial Oil Characterization of Irvingiagabonensis Seed - (:unkn) unknown (My University, 2025)
Background and Objective: African mango (Irvingiagabonensis) commonly known as Bush Mango, is a treebelongingtothe genus Irvingia. The fruits of these trees are valued for their fats- and protein- rich nuts. The nutritional value of African mango seed (Irvingiagabonensis) is estimated to contribute to human health and food consumption safety. This research work is aimed to highlighting the Antioxidant activity and partial oil characterization of African mango seed (Irvingiagabonensis). Materials and Methods: The antioxidant activity and partial oil characterization were analyzed using standard laboratory methods. Results: The antioxidant results obtained showed that the sample had its highest antioxidant activity as follows: Hydroxyl scavenging activity at 73%, ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid)) scavenging at 67%, superoxide scavenging activity at 60%, ferric reducing antioxidant power activity at 4.8% and nitric acid scavenging activity at 3.6%. The partial oil characterization result shows as follows: Saponification (mgKOH/kg) (323.514.118), Boiling point (3222.00), Flash point (2461.732), Viscosity (164.32.157), Iodine value (104.8600.381), Cloud point (12.40.02), Peroxide (mleq/kg) (10.20.02), Melting point (6.30.015), Acid value (%) (4.1830.036), Free Fatty acid (%) (2.0920.018), Refractive index (1.4210.001), Specific gravity (0.93010.007). Conclusion: This study showed that African mango seed exhibit effective antioxidant property and contain adequate oil componentsthus making it fit and edible for consumption.
Keywords: African Research